The stakes of the EPA between the EU and the ACP states : implications for West Africa and Burkina Faso - (:unkn) unknown (My University, 2019)
Economic relations between the European Union (EU) and the African, Caribbean and Pacific Group of States (ACP) have been characterized by non-reciprocal preferential trade agreements. These trade agreements have been continuously criticized for being incompatible with WTO rules. In order to conform to the norms of international trade, the EU has required that its economic relations with the ACP states are governed by the Economic Partnership Agreements (EPA), which are negotiated with three African Regional Economic Communities. After more than twelve years of negotiations, the countries of the Economic Community of West African States (ECOWAS) have signed the EPA with the EU, despite differing opinions on the real benefits that can be expected from such agreements. The aim of this thesis is to evaluate the impact of the EPA on the economies of the ECOWAS (in terms of trade creation and diversion), in particular Burkina Faso. The study uses a modified version of the computable general equilibrium model developed in Decaluwé et al. (2013). The static baseline model is calibrated using a social accounting matrix (SAM) for Burkina Faso’s economy of 2012. Our results show that the APE give the EU a competitive advantage. Burkina Faso’s imports originating from the EU increase, manifesting trade diversion. The trade agreements have no significant effect on Burkina Faso’s exports to the EU or the ECOWAS. Furthermore, while the APE considerably improve population well-being, they do not lower poverty or social inequalities.
Keywords: African Research